ELEKTROKOAGULASI MONOPOLAR UNTUK MENYISIHKAN ORGANIK DAN MINYAK LEMAK AIR BUANGAN DOMESTIK (GREY WATER) - Ansiha Nur; Agus Jatnika (Universitas Andalas, 2017)
Electrocoagulation is an electrochemical technology to treat organic and inorganic wastewater without the use of chemicals so as not to increase the burden of environmental pollution. Electrocoagulation performance is influenced by electrode type, current density and number of electrodes. The purpose of this research is to know the effectiveness of COD and oil grease removal from domestic waste water (grey water) through electrocoagulation process. The experiment was conducted in batch using monopolar electrode configuration, with aluminum electrodes 95,7%. In this research, electric current density 21-104 A/m2, detention time and pH were varied. The optimum condition was obtained at current density of 104 A/m2 for 15 minutes with COD and oil grease removal consecutively are 87.48% and 77.50%. The result of this electrocoagulation process shows COD and oil grease concentration of 15.02 mg/L and 4.20 mg/L are under the standard of Ministry of Environment Decree No. 112 Year 2011 grade 3, to be used for watering plants and flushing the hotel toilet.Keywords: electrocoagulation, aluminum electrode, monopolar, current density, grey waterABSTRAKElektrokoagulasi merupakan teknologi elektrokimia untuk mengolah limbah organik dan anorganik tanpa menggunakanbahan kimia sehingga tidakmenambah bebanpencemaran lingkungan.Kinerja elektrokoagulasi dipengaruhi oleh jenis elektroda,kerapatanarusdan jumlah elektroda.Tujuanpenelitian ini untuk mengetahuiefektifitas penurunan organik (COD) dan minyak lemak dari airbuangan domestik (grey water) melalui proses elektrokoagulasi. Percobaan dilakukan secara batch menggunakan konfigurasi susunan elektroda monopolar, dengan jenis elektrodaberupaplat alumunium 95,7%.Variasi penelitian pada reaktor batch adalah terhadap kerapatan arus listrik21-104 A/m2, waktu detensi dan pH.Kondisi optimum diperoleh pada kerapatan arus 104 A/m2pada menit ke-15 denganpenyisihanCOD dan minyak lemakyaitusebesar 87,48% dan 77,50%. Hasil proses elektrokoagulasiini menunjukkan nilai COD sebesar 15,02 mg/L dan minyak lemak 4,20 mg/Lberada di bawah baku mutu Keputusan Menteri Negara Lingkungan Hidup Nomor 112 Tahun 2011kelas 3, untuk dimanfaatkan untuk penyiraman tanaman dan penggelontoran toilet hotel.Kata kunci: elektrokoagulasi, elektroda aluminium, monopolar, kerapatan arus, grey water